Bolivia : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This papers reviews economic developments in Bolivia during the 1990s. During 1992-94, real GDP grew by 3.8 percent a year on average-consistent with real per capita growth of 1.7 percent a year-despite the adverse effects of weather conditions on agricultural output and a substantial deterioration in the terms of trade in 1992. The overall deficit of the combined public sector fell from 3.2 percent of GDP in 1994 to 2.0 percent of GDP in 1995, partly reflecting a slower-than-envisaged pace of structural reforms.